Cycling hypoxia induces chemoresistance through the activation of reactive oxygen species-mediated B-cell lymphoma extra-long pathway in glioblastoma multiforme. Issue 1 (December 2015) - Chen, Wei-Ling; Wang, Chi-Chung; Lin, Yu-Jung; Wu, Chung-Pu; Hsieh, Chia-Hung
Abstract Background Cycling hypoxia is a well-recognized phenomenon within animal and human solid tumors. It contributes to the resistance to cytotoxic therapies through anti-apoptotic effects. However, the mechanism underlying cycling hypoxia-mediated anti-apoptosis remains unclear. Methods Reactive oxygen species (ROS) production, activation of the hypoxia-inducible factor-1 alpha (HIF-1α) and nuclear factor-κB (NF-κB) signaling pathways, B-cell lymphoma extra-long (Bcl-xL) expression, caspase activation, and apoptosis in in vitro hypoxic stress-treated glioblastoma cells or tumor hypoxic cells derived from human glioblastoma xenografts were determined by in vitro ROS analysis, reporter assay, western blotting analysis, quantitative real-time PCR, caspase-3 activity assay, and annexin V staining assay, respectively. Tempol, a membrane-permeable radical scavenger, Bcl-xL knockdown, and specific inhibitors of HIF-1α and NF-κB were utilized to explore the mechanisms of cycling hypoxia-mediated resistance to temozolomide (TMZ) in vitro and in vivo and to identify potential therapeutic targets. Results Bcl-xL expression and anti-apoptotic effects were upregulated under cycling hypoxia in glioblastoma cells concomitantly with decreased responses to TMZ through ROS-mediated HIF-1α and NF-κB activation. Tempol, YC-1 (HIF-1 inhibitor), and Bay 11-7082 (NF-κB inhibitor) suppressed the cycling hypoxia-mediated Bcl-xL induction in vitro and in vivo. Bcl-xL knockdown and Tempol treatment inhibited cycling hypoxia-induced chemoresistance. Moreover, Tempol treatment of intracerebral glioblastoma-bearing mice combined with TMZ chemotherapy synergistically suppressed tumor growth and increased survival rate. Conclusions Cycling hypoxia-induced Bcl-xL expression via ROS-mediated HIF-1α and NF-κB activation plays an important role in the tumor microenvironment-promoted anti-apoptosis and chemoresistance in glioblastoma. Thus, ROS blockage may be an attractive therapeutic strategy for tumor microenvironment-induced chemoresistance.